Socioscientific Issues in Science Education: The Case of Turkey - Topcu, Mustafa Sami; Mugaloglu, Ebru Zeynep; Guven, Devrim (EDAM, 2014)
The purpose of this study is to identify the foci and results of studies on socioscientific issues (SSI) conducted in Turkey. Additionally, the study aimed to compare the results of this study with ones conducted internationally. For this aim, a literary review of empirical studies related to SSI conducted in Turkey was carried out. Four criteria were used to identify the research studies included in this review: studies which are contemporary (2002- 2012), were conducted in Turkey (sampling Turkish populations), which focus on SSI in science education, and which used first-hand data gathered through empirical investigations. Related databases were searched using SSI and Turkey and SSI and Turkish keywords in both English and Turkish. The search resulted in 13 empirical research articles and 17 Master's and Doctoral theses. After the initial review of the studies based on the established criteria, 11 articles and 13 theses were identified for inclusion in this review. The results showed that SSI related studies conducted in Turkey, similar to international studies, have two roles. While the aim was to teach SSI in some studies, in other studies, SSI were used as a context to reach other broader, science education related aims. Studies mostly focused on the knowledge of pre-service science teachers regarding various SSI, the self-efficacy beliefs of teaching and the informal reasoning skills in the context of SSI. The majority of the studies were master's theses. Another important point that needs to be paid attention to is that SSI related studies in Turkey tended to employ quantitative methods while very few studies utilized in-depth qualitative methods.
Keywords: Socioscientific Issues; Literature Review; Turkey; Teacher Education; Science Education; SOCIO-SCIENTIFIC ISSUES; STUDENTS ARGUMENTATION; DECISION-MAKING; TEACHERS PERCEPTIONS; CONTENT KNOWLEDGE; INSTRUCTION; PATTERNS; CONTEXT; Education & Educational Research